Language Education and Systemic Functional Linguistics : A State-of-the-art-review (Universitas Islam Negeri Sunan Ampel Surabaya, 2020)
The purpose of the present paper is to offer a state-of-the-art review on the topic of Systemic Functional Linguistics (SFL) and its theoretical and practical implications on the field of language education, being the former widely recognized due to its potentiality to encourage both reflection and action for the participants involved. Recent empirical studies were located and thoroughly reviewed, which shed light on the three most researched areas including text analysis and literacy intervention, classroom discourse, and the language teaching and learning processes. As a final remark and taking into account the literature analysis, some prospective studies are briefly proposed.